Development of android application-based learning media for English subjects - Andi Asmawadi; Pattaufi Pattaufi; Abdul Hakim; Nurhikmah H (Inovasi Kurikulum, 2025)
The limited availability of interactive learning media and contextual learning resources, especially for English subjects that require audio-visual support such as language laboratories, forms the basis of this study. This research aims to develop Android-based learning media for seventh-grade English subjects at SMPN 5 Labakkang. This study employs the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The media was developed using PowerPoint and iSpring Suite, then converted into an APK file using Website 2 APK Builder. Validation was conducted by subject matter experts and media experts, with results indicating that the media is highly feasible. A trial was conducted with 20 students using pretests and posttests. The results showed a significant improvement in students' learning outcomes after using the media, with an average score increase of 27 points. In addition, both students and teachers responded positively regarding the ease of use and effectiveness of the media. This study concludes that the developed Android-based learning media are effective in improving students' understanding of English and can serve as an alternative interactive teaching resource for junior high schools.   Abstrak Keterbatasan media pembelajaran interaktif dan sumber belajar kontekstual, terutama untuk Bahasa Inggris yang memerlukan dukungan audio-visual seperti laboratorium bahasa. Tujuan penelitian untuk mengembangkan media pembelajaran berbasis Android pada mata pelajaran Bahasa Inggris kelas VII di SMPN 5 Labakkang. Penelitian ini menggunakan model pengembangan ADDIE yang terdiri dari lima tahap, yaitu Analyze, Design, Develop, Implement, dan Evaluate. Media dikembangkan menggunakan PowerPoint, iSpring Suite, dan dikonversi menjadi file APK menggunakan Website 2 APK Builder. Validasi dilakukan oleh ahli materi dan ahli media, dengan hasil validasi menunjukkan bahwa media tergolong sangat layak. Uji coba dilakukan pada 20 peserta didik melalui pretest dan posttest. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam hasil belajar peserta didik setelah menggunakan media, dengan peningkatan skor rata-rata sebesar 27 poin. Selain itu, peserta didik dan pendidik memberikan tanggapan positif terhadap kemudahan penggunaan dan keefektifan media. Penelitian ini menyimpulkan bahwa media pembelajaran berbasis Android yang dikembangkan efektif meningkatkan pemahaman peserta didik dalam pembelajaran Bahasa Inggris dan dapat digunakan sebagai alternatif bahan ajar interaktif di sekolah menengah pertama. Kata Kunci: aplikasi android; bahasa Inggris; media pembelajaran; model ADDIE